2010
DOI: 10.1039/b924679g
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the selective staining of chromosomal DNA in dividing cells using a luminescent terbium(iii) complex

Abstract: The emission intensity of a monocationic Tb or Eu(III) complex of a bis(1-azaxanthone) ligand is enhanced in the presence of serum albumin; the lanthanide complex stains dividing cells, allowing visualisation of mitotic chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Barton and Gilles also found that Ru(II) polypyridyl complexes not only exerted biological effects but also could be the luminescence cellular imaging probes, specially for RNA mismatches [18,28e30]. Meanwhile, Che et al found that Au(III) complexes containing N-heterocyclic carbene ligands could be the thiol "switch-on" fluorescent probes and anti-cancer agents [31], while Parker et al observed the selective staining of chromosomal DNA in dividing cells using a luminescent Tb(III) complex [32]. Importantly, Vicente et al found that the intracellular localization of the Zn(II)-phthalocyanines determined their photodynamic activity [33].…”
Section: Introductionmentioning
confidence: 98%
“…Barton and Gilles also found that Ru(II) polypyridyl complexes not only exerted biological effects but also could be the luminescence cellular imaging probes, specially for RNA mismatches [18,28e30]. Meanwhile, Che et al found that Au(III) complexes containing N-heterocyclic carbene ligands could be the thiol "switch-on" fluorescent probes and anti-cancer agents [31], while Parker et al observed the selective staining of chromosomal DNA in dividing cells using a luminescent Tb(III) complex [32]. Importantly, Vicente et al found that the intracellular localization of the Zn(II)-phthalocyanines determined their photodynamic activity [33].…”
Section: Introductionmentioning
confidence: 98%
“…was synthesised according to previously described methods. 137 Complexation was confirmed by mass spectrometry prior to working up the reaction. The complex was then purified by preparative HPLC and isolated as an off-white solid.…”
Section: Studies Using Circular Dichroismmentioning
confidence: 99%
“…This was an unexpected result, as the q' value given in the literature for the racemic parent complex [Ln.L 22 ] + was ~ 0 for both the europium and terbium analogues. 137 The reproducibility of this literature result was subsequently investigated; using the methodology outlined for the complexes of L…”
Section: Estimation Of the Complex Hydration State Q'mentioning
confidence: 99%
“…Based on this intercalative mechanism, many cationic planar, polycyclic dyes derived from quinolizinium, benzooxazolinium, benzothiazolinium, and acridizinium have been developed as powerful optical probes for DNA detection [9,10]. These DNA-selective probes demonstrate a variety of potential applications in pharmaceutical studies and molecular biology, and can be used as probes for electron and/or energy transfer and gene modulators [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%